Developing Problem Based Learning Device to Grow Students' Mathematical Critical Thinking Ability - Muhamad Julfianto; Elfis Suanto; Syarifah Nur Siregar (Jurnal Gantang, 2022)
This research is motivated by the importance of students' mathematical critical thinking skills and the limited learning tools with problem-based learning models to facilitate students' mathematical critical thinking skills used by teachers (Syllabus, RPP, and LAS) as a means of supporting learning in the 2013 Curriculum and fostering the ability to think mathematical critical. This research aims to produce a learning device based on the Model of Problem-Based Learning (PBL) on the probability material that is valid and practical to grow students' mathematical critical thinking skills. The model of development used is the 4D model (Define, Design, Develop, Disseminate). The subjects of one-to-one evaluation in this study were three 9th-grade SMP IT Aufia Global Islamic Boarding School and six heterogeneous students as small group evaluation subjects. The data analysis technique that will be carried out in this study is descriptive analysis technique. The Instruments used include (1) Syllabus, lesson plans, and student activity sheet validation sheets; and (2) a Questionnaire for student response to Student activity sheets. The learning tools that have been compiled are then validated by three validators and revised according to suggestions from the validators. The learning device is said to be valid if the level of validity achieved is at a value The validation results from three validators show that the syllabus, lesson plans, and student activity sheet are very valid, with the average score in a row 3.82, 3.74, and 3.55. Student activity sheet practicality shows an average percentage of 92,06% with efficient criteria. The results of this study indicate that the learning based on Model Problem-Based Learning (PBL) on the probability material is very valid and significantly grows students' mathematical critical thinking skills.